Interlinkages between the right to development and the right to freedom of movement - Nika Buzaladze (RUDN Journal of Law, 2014)
Migration had become a subject of an active inter-state dialogue during the last two decades. The first such high level dialogue on international migration and development took place in 2006. Migration and development are highly interdependent processes.The article analyses their interlinkages.